“Dentinal Microcracks After Root Canal Preparation” A Comparative Evaluation with Hand, Rotary and Reciprocating Instrumentation - Priya, N. Tulasi (J Clin Diagn Res, 2014)
Introduction: The purpose of this study was to compare the incidence of dentinal micro cracks after instrumentation with various types of NiTi files in rotary and reciprocating motion. Materials and Methods: One hundred human extracted mandibular central incisors were taken and divided into 10 groups (n=10 teeth per group). Group 1- No preparation, Group 2 – Hand instrumentation, Groups 3,4 - ProTaper files in rotary and reciprocating motion, Groups 5,6 - ProTaper Next files in rotary and reciprocating motion, Groups 7,8 – Oneshape files in rotary and reciprocating motion, Groups 9,10 – Reciproc files in rotary and reciprocating motion. Specimens were sectioned horizontally at 3,6 and 9 mm from the apex and dentinal micro cracks were observed under a stereomicroscope. Results: There was a statistically significant difference between the groups (p<0.05). There were no significant differences in crack formation between the groups (Protaper Next - Rot, Protaper Next - Rec, Reciproc – Rec); (ProTaper - Rot, ProTaper - Rec, Oneshape – Rot), (Oneshape – Rot, Reciproc – Rot), (One shape Reciproc, Reciproc – Rec); (p >.05). Conclusion: Least cracks were seen in canals instrumented with Pro Taper Next files both in rotary and reciprocating motion. Full sequence rotary systems showed less cracks than single file systems and full sequence rotary systems showed less cracks in reciprocating motion than in rotary motion.